Transforming Healthcare: The Power of Artificial Intelligence - Khayru, Rafadi Khan (Bulletin of Science, Technology and Society, 2022)
Technology has revolutionized almost every aspect of modern life, including the way we approach and receive medical care. The purpose of this literature is to demonstrate the significant contributions that technology has made and continues to make to making quality healthcare accessible and efficient for all individuals. The literature search used Google Scholar from 2017. Using some specific criteria, the results were analysed and concluded with a deductive method. Realizing the true potential benefits of AI requires cross-industry collaboration and actively engaging patients and providers. Ultimately, our research shows that while progress has been made towards achieving AI-powered healthcare decision support that improves workflows and reduces the burden on practitioners, Further development can be focused on data and infrastructure security, ethical integration and comprehensive public accessibility, regulation of AI use, and the development of transparent and accountable AI design.